Best Practices for Using Telehealth in Hospice and Palliative Care. Issue 3 (8th June 2021) - Webb, Michelle; Hurley, Susan Lysaght; Gentry, Jennifer; Brown, Melanie; Ayoub, Cynthia
Abstract : Hospice and palliative care providers throughout the United States have continued to provide compassionate patient- and family-centered care during the COVID-19 (coronavirus disease 2019) pandemic while adapting to the need for scrupulous infection control measures and the accelerated use of telehealth. Prior to the pandemic, hospice and palliative care adopted telehealth slowly compared with other specialties, but its rapidly increasing utilization during the COVID-19 pandemic has long-term implications for access to primary and specialty palliative care, particularly for patients in rural communities and populations experiencing inequitable access to services. Telehealth also shows great promise for leveraging technology to provide care more effectively and efficiently. As more provider organizations become equipped with telehealth infrastructure, and as advocacy for broader reimbursement of these services grows, telehealth services for hospice and palliative care are expected to continue. This article highlights the work of expert clinicians from multiple hospice and palliative care organizations to develop best practices for conducting telehealth visits in inpatient and community settings. The authors propose that best practices be compiled and considered to ensure quality-driven, evidence-based clinical practice guidelines with interprofessional applicability.